Accurate hydrogenated vegetable oil viscosity predictions for monolith reactor simulations. (16th March 2020) - Albrand, Pierre; Julcour, Carine; Gerbaud, Vincent; Billet, Anne-Marie
Graphical abstract: Highlights: Contribution group model to predict viscosity of partially hydrogenated edible oils. CFD simulations of a three-phase catalytic monolith reactor with viscosity change. Investigation of two-way coupling between hydrodynamics, transport and reaction. Strong limitations by mass transfer of fatty acids highlighted. Reactor performances greatly impacted by the evolution of viscosity and diffusivity. Abstract: The viscosity of edible oils was measured before and after hydrogenation to assess a new model for predicting the viscosity of partially hydrogenated oils with given saturation degree and temperature. This contribution group model is based on a semi-predictive approach, and can be used to estimate viscosity changes due to hydrogenation. It was experimentally validated using three different oils, and the results show an overall relative average deviation of 3.7%. The model was implemented in a transient CFD simulation of a three-phase monolith catalytic reactor for edible oil hydrogenation. Hydrogenation in Taylor flow was described with the unit cell approach. The influence of viscosity changes on the reaction yield and selectivity were investigated in relation with the coupling between hydrodynamics, mass transfer, and reaction kinetics. This effect proved to be significant in the former case; the reactor length was increased by a factor 1.5, yielding approximately 30% conversion.